About the sense of will in human action (Mayéutica Revista Científica de Humanidades y Artes, 2024)
The following essay will try to reflect on the guiding sense of the will in human action. The theoretical proposal is based on the postulates of Aristotle, Immanuel Kant, Friedrich Nietzsche and Paul Ricœur who, from their own thought systems,approached the notion of will, in light of their natural moral sense. The methodology follows its course under the mediation of the Philosophical Hermeneutics proposed by Hans Gadamer, from whom we return to the vital importance of language in the processes of comprehension and interpretation of texts and of life itself; in a complementary way, Ricœur's practical Philosophy and teleological ethical sense are considered, given the need to articulate the theoretical input of these reflections to the field of human action.
Keywords: will; ethics; morality; human action; teleology